METAPHORICAL LANGUAGE IN ENGLISH AND UZBEK: A COGNITIVE LINGUISTIC APPROACH (Modern education and development, 2025)
This article explores metaphorical expressions in English and Uzbek through the lens of cognitive linguistics. Metaphors are not merely poetic devices but essential tools for human thought and communication. Based on Lakoff and Johnson's conceptual metaphor theory, the study analyzes how abstract concepts such as time, emotion, and life are metaphorically constructed in both languages. The research highlights universal and culture-specific metaphors, showing how cultural experiences shape linguistic metaphors. This comparative analysis has implications for translation, bilingual education, and intercultural understanding.